Comparing the role of perceived burdensomeness and thwarted belongingness in prospectively predicting active suicidal ideation. Issue 2 (2nd December 2022) - Jacobucci, Ross; McClure, Kenneth; Ammerman, Brooke A.
Abstract: Objective: The Interpersonal Theory of Suicide has been foundational in guiding current suicide literature. Despite recent research underscoring fluctuations of suicidal ideation within hours, there have been few studies examining the key constructs of perceived burdensomeness and thwarted belongingness within an intensive framework. Thus, the current study aimed to add cumulative knowledge regarding the within‐person relationship between perceived burdensomeness, thwarted belongingness, and active suicidal ideation as assessed within an ecological momentary assessment design. Method: A final sample of 35 individuals with a past‐year history of suicidal thoughts or behaviors completed brief surveys four times per day for 30 days. Results: Findings highlighted that the addition of covariates may offer small improvements in modeling subsequent suicidal ideation, while controlling for SI at the prior time. Further, both thwarted belongingness and perceived burdensomeness were associated with next timepoint suicidal ideation, and their interaction added little incremental value. Conclusion: Findings demonstrate the potential importance of thwarted belongingness in predicting suicidal ideation. Further, results highlight that the main effects of thwarted belongingness and perceived burdensomeness, rather than their interaction, may be more important to consider in relation to active suicidal ideation.